Urban visual-spatial intelligence: linking human and sensor perception for sustainable urban development - Weng, Qihao; Hou, Qianbao; Chen, Zhixing; Benediktsson, Jón Atli; Gamba, Paolo; Tuia, Devis; Zhang, Fan; Xu, Yonghao; Wu, Meiliu; Li, Na; Batty, Michael (npj Urban Sustainability, 2025)
Understanding urban perception enhances urban intelligence research, aiding sustainable development and smart city. Urban Visual-Spatial Intelligence (UVSI) integrates human and sensor perception. This Perspective explores UVSI’s potential for sustainable development, identifies research gaps, and outlines future priorities. Advances in AI, high-performance computing, real-time data processing, and citizen science could significantly impact UVSI. Key research areas include spatiotemporal data integration, visual analytics, ethical frameworks, and inclusive methodologies for AI-driven urban management.